Level of Community Participation in Prevention To Forest and Land Fires in the District Ulin Landing in Banjarbaru City - Pangestu, Muhammad Sigit; Angriani, Parida; Hastuti, Karunia Puji; Adyatma, Sidharta; Aristin, Nevy Farista (JPG (Jurnal Pendidikan Geografi), 2025)
Forest and land fires affected Indonesia from January to August 2023, burning a total of 267,935.59 hectares across 38 provinces. In South Kalimantan Province, the fires ranked 4th in severity, with a total of 24,588 hectares burned. The El Niño phenomenon in 2023 contributed to the occurrence of these forest and land fires, while human activities, such as land clearing, also played a role. In South Kalimantan Province, forest and land fires occurred in 13 districts/cities, including Banjarmasin, Banjarbaru, Banjar, Tapin, South Hulu Sungai, Central Hulu Sungai, North Hulu Sungai, Balangan, Tabalong, Barito Kuala, Tanah Laut, Tanah Bumbu, and Kotabaru. The province has four districts/cities classified as high-risk areas for forest and land fires: Banjarbaru City, Tanah Laut Regency, Banjar Regency, and Barito Kuala Regency. A particularly vital area in this region is Syamsudin Noor Airport, located in Syamsudin Noor Subdistrict, Landasan Ulin District. According to the South Kalimantan BPBD Operations Control Center, the highest number of forest fire incidents occurred in Banjarbaru City. The total burned area reached 1,015.03 hectares between March and November 2023, with incidents recorded as follows Landasan Ulin District 206 incidents (452.53 hectares), Liang Anggang District: 98 incidents (238.02 hectares), Cempaka District: 115 incidents (278.69 hectares), North Banjarbaru District: 17 incidents (29.32 hectares), South Banjarbaru District: 22 incidents (16.48 hectares). The objective of this research is to analyze the level of public participation in forest and land fire prevention in Landasan Ulin District. The study examines factors such as controlled burning practices, removal of flammable materials, and timing of land clearing activities. This study employs a descriptive quantitative method, using percentage calculations and average questionnaire values to process and interpret the collected data. The findings indicate that public participation in forest and land fire prevention in Landasan Ulin District falls into the "Moderate" category, suggesting a sufficient level of involvement in fire prevention efforts.